Desempenho de milho grão e silagem consorciado com diferentes plantas de cobertura - Sant'Ana, André Lucas (2017)
Consortium cultivation between species aims to optimize the use of the area and bring some advantages, such as anticipation of pasture formation, post-silage soil cover, corn grain harvest, anticipation of grazing, and increased biomass production. , Intercropping can compete on maize, affecting its productive potential. In this sense, the objective of this work was to evaluate the effects and yields of the intercropping between maize crop in the first crop and forage crops, with direct sowing at the same time of maize sowing using a continuous flow system and a double disc disconcerted for deposition Of the seeds, as well as to determine which of the four species is the best species to submit to the consortium, for multiple purposes: whole plant silage and straw formation in the system. The treatments consisted of maize consortium and four species of cover plants. The experiment was conducted under field conditions, crop 2015/2016, in the experimental area of the Technological University of Paraná (UTFPR), Campus of Two neighbors. The experimental design was a randomized complete block design with five treatments and four replications. The evaluations consisted of plant height at V7, spike insertion height, final height, stem diameter, number of rows per spike, grains per row, grain per ear, mass of a thousand grains, population, yield, green biomass production And total dry matter and accumulated total biomass production, silage bromatological analysis. The final grain yield of corn was not influenced by the cropping system and cover crops. For the production of silage, and its composition bromatológica, did not occur significant differences between the conventional system and the consortium. Remembering that the adoption or not of the intercropping system if the production is only for grains and silage, only if it is carried out in a harvest, for a production seeking a greater coverage of the soil, in order to reduce future costs the use of intercropping has its viability.